Developing "MAGIC SAGA" Game as a Medium for Enriching Vocabulary of Eleventh Graders - Sari, Dewi Puspita (RETAIN : Journal of Research in English Language Teaching, 2021)
This study aimed to describe the development process, including the quality validation and the practicality of the ’Magic Saga’ game as a medium for enriching the vocabulary of eleventh graders. This study adopted the ADDIE approach by Branch (2009) to develop the media. This study took place at a high school by involving eight students and one teacher to test the game’s practicality. On the other hand, one of the English lecturers validated the quality of the game. The validation score for content and design was 3.98 that categorized as ’excellent.’ Based on observation and interview results; the students showed attractive interactions. Also, they gave good comments toward the Magic Saga game. Moreover, Students said that they were motivated to learn and practice vocabulary. Magic Saga game got good appraisal from the teacher and also a lecturer. While playing the game, the primary goals had met, and it concluded that the Magic Saga game was applicable for the English teaching and learning process.